2012
DOI: 10.1292/jvms.12-0103
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Serological Survey of Caprine Arthritis-Encephalitis Virus (CAEV) in Korean Black Goats (<i>Capra hircus aegagrus</i>)

Abstract: ABSTRACT. A national serological survey of caprine arthritis-encephalitis virus (CAEV) infection was conducted using an enzyme-linked immunosorbent assay (ELISA) and an agar gel immunodiffusion (AGID) test. A total of 658 black goats of various breeds were sampled from 59 farms in three regions of Korea. The CAEV-positive goats were predominantly detected in the Southern region (n=17) as compared with the Northern (n=1) and Central regions (n=0) (χ 2 =6.26, P=0.044). Among 658 goats tested, 18 were positive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Nearly all the commercial dairy goat farms in Taiwan use incompletely pasteurized bulk milk to feed their lambs, whereas for meat goats, whose lambs are fed right from their mother. The former feeding strategy used in dairy goat farm may accelerate the spreading of diseases [ 13 , 14 ]. Previous studies have suggested that the longer lifespan of dairy goats combined with their close proximity to each other may cause this high CAEV prevalence rate in dairy goat farms [ 1 , 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all the commercial dairy goat farms in Taiwan use incompletely pasteurized bulk milk to feed their lambs, whereas for meat goats, whose lambs are fed right from their mother. The former feeding strategy used in dairy goat farm may accelerate the spreading of diseases [ 13 , 14 ]. Previous studies have suggested that the longer lifespan of dairy goats combined with their close proximity to each other may cause this high CAEV prevalence rate in dairy goat farms [ 1 , 15 ].…”
mentioning
confidence: 99%
“…Besides, very high herd seropositivity for CAEV has been reported in the U.S.A. (73%) [ 4 ], Australia (82%) [ 5 ] and Brazil (35%) [ 2 ]. Among the neighboring countries of Taiwan, the seroprevalence of CAEV was 10% in a total of 857 goat serum samples in Japan [ 7 ], compared to only 2.73% of goats in South Korea [ 14 ]. In China, the CAEV seropositive rates varied from 0.2 to 30% [ 16 ].…”
mentioning
confidence: 99%
“…The caprine arthritis encephalitis virus (CAEV) from the genus Lentivirus, first isolated in 1980 (Crawford et al, 1980), is the agent of the chronic disease defined as caprine arthritis encephalitis (CAE). This disease is a problem around the world, with high CAEV prevalence reported in various goat populations, including 98.5, 80.4, 51.6, 23.2, 28.6, 10.3, 82.0, 73.0, 18, 35.3, 35.4 to 81.1, and 21.9% of herds (or animals) infected in Taiwan, Canada, Lebanon, Jordan, Mexico, the United Kingdom, Australia, the United States, Spain, Egypt, Poland, and Croatia, respectively (Dawson and Wilesmith, 1985;Grewal et al, 1986;Cutlip et al, 1992;Al-Qudah et al, 2006;Vallerand et al, 2007;Ghanem, 2011;Oem et al, 2012;Martínez-Navalón et al, 2013;Stonos et al, 2013;Jones, 2014;Tabet et al, 2015;Tariba et al, 2015;Waseem et al, 2015;Thomann et al, 2017;Yang et al, 2017;Gruszecki et al, 2018). This disease causes major economical and welfare problems for the worldwide goat industry, including reduced production, growth rate, and longevity; greater rate of reproductive failures; premature culling; and increased incidence of disease (Smith and Cutlip, 1988;Peterhans et al, 2004;Reina et al, 2009;Leitner et al, 2010;Murphy et al, 2010;Konishi et al, 2011;Kaba et al, 2012;Tageldin et al, 2012;Martínez-Navalón et al, 2013).…”
Section: Short Communicationmentioning
confidence: 99%
“…These viruses are widespread worldwide with the exception of New Zealand and Australia, which are considered free of SRLV A, and Iceland, which eradicated SRLV after a devastating epizootic outbreak originating from the import of SRLV-infected karakul sheep in the early 1930s. [12][13][14][15][16][17][18][19][20] Genotype B, and in particular the B1 subtype, is considered the most virulent genotype for goats, whereas in sheep genotype A is the principal cause of clinical manifestations. 2 6 SRLVs are known to be the cause of a chronic multisystemic inlammatory disease characterised by a long incubation period and a lifelong persistent infection.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy are the findings of several authors reporting genomic sequences from sheep with higher identities to CAEV than to MVV, 9–11 indicating a possible common ancestral genotype. These viruses are widespread worldwide with the exception of New Zealand and Australia, which are considered free of SRLV A, and Iceland, which eradicated SRLV after a devastating epizootic outbreak originating from the import of SRLV‐infected karakul sheep in the early 1930s 12–20 . Genotype B, and in particular the B1 subtype, is considered the most virulent genotype for goats, whereas in sheep genotype A is the principal cause of clinical manifestations 2 6 …”
Section: Introductionmentioning
confidence: 99%